Model Institutional Transformation of The Banten Provincial Government Toward “Golden Banten 2045” - Sururi, Ahmad; Iriany, Ieke Sartika; Pasciana, Rostiena (Faculty of Social and Political Science Universitas Brawijaya, 2026)
This study aims to analyze the institutional transformation model of the Banten Provincial Government toward Golden Banten 2045 through the perspectives of local government institutional transformation, governance analysis, and institutional model analysis. This research employed a descriptive qualitative method, with data collected through interviews and literature review. The data were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that the institutional structure of the Banten Provincial Government remains categorized as a hierarchical government, characterized by limited network management capacity, weak collaboration with the private sector, and suboptimal governance performance. The novelty of this study lies in the formulation of a local government institutional transformation model that integrates agile government and networked government as a strategic shift from a hierarchical, sectoral, and rule-driven bureaucracy toward an adaptive, collaborative, thematic, cross-sectoral, people-driven, and locally empowered institutional arrangement. The study implies that achieving Golden Banten 2045 cannot rely solely on administrative bureaucratic reform, but requires an institutional design capable of strengthening collaborative capacity, policy responsiveness, and alignment between bureaucratic reform and regional competitiveness.